PERANCANGAN APLIKASI SISTEM MANAJEMEN DOKUMEN DAN PENCARIAN TEKS DENGAN MENGGUNAKAN OPTICAL CHARACTER RECOGNITION(OCR) - Maulana Sandy Dermawan; Bagus Mulyawan; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
This application aims to make the mail manager more practical and safe because the management system and the letter using the web-based OCR. This application is made with the System Development Life Cycle (SDLC) waterfall model through stages, namely the planning stage, the analysis phase, the design stage, the programming stage, and the testing phase. With this application can help archive letters in digital form (image file) by selecting the desired digital letter, then the application will convert the image form into character with the Optical Character Recognition method with the help of tesseract library so that all the text in the image can be converted well into the form of characters, then can be stored into the database and can do a search with certain keywords then the application will search the database for these keywords and then bring up the search results easily & quickly. At the end of this research the author concluded that this application can help speed up & make practical the search process for digital archive letters.